MB-GNG: Addressing drawbacks in multi-objective optimization estimation of distribution algorithms - Martí, Luis; García, Jesús; Berlanga, Antonio; Coello Coello, Carlos A.; Molina, José M. (Operations research letters, 2011)
We examine the model-building issue related to multi-objective estimation of distribution algorithms (MOEDAs) and show that some of their, as yet overlooked, characteristics render most current MOEDAs unviable when addressing optimization problems with many objectives. We propose a novel model-building growing neural gas (MB-GNG) network that is specially devised for properly dealing with that issue and therefore yields a better performance. Experiments are conducted in order to show from an empirical point of view the advantages of the new algorithm.